Laterality of the legs in young female soccer players - Antosiak-Cyrak, K. Z.; Wiczynski, G.; Rostkowska, E. M. (Human Movement, 2015)
Purpose. The aim of the present study was assessment of laterality of the legs of young female soccer players and their non-training counterparts. Methods. The study sample comprised 9 female soccer players and 19 non-training girls. They underwent three measurement sessions, one every six months. The applied tests included kinesthetic differentiation, rate of local movements, static balance, single-leg hop, rate of global movements, strength and speed, and functional asymmetry of the legs tests. Results. The soccer players were better than the controls in their performance of the rate of local movements, rate of global movements, kinesthetic differentiation, single-leg 15m timed hop and static balance tests. Smaller differences between the results of the left and the right legs in soccer players, than in non-training girls, were noted in the rate of local movements, rate of global movements and kinesthetic differentiation tests. In the static balance test, the differences were greater in the group of soccer players. Conclusions. Lateralization of the lower limbs is a highly complex characteristic with a different variability in athletes than in nontraining individuals. The results of the present study also point to the specialization of soccer players` left legs in body balance and single-leg hop tests.